2005
DOI: 10.1016/j.ejcts.2004.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Valvular surgery in octogenarians: operative risks factors, evaluation of Euroscore and long term results

Abstract: Valvular surgery in octogenarians is a safe and low risk procedure compared to functional benefit and long-term survival. Our data how that logistic Euroscore overestimates the mortality in this high-risk group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
69
3
15

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 15 publications
9
69
3
15
Order By: Relevance
“…Multivariate logistic regression analysis showed that the only preoperative risk factors associated with operative mortality were urgent procedure, associated coronary artery surgery, NYHA functional class, and previous percutaneous valvuloplasty. While Collart et al [11] did not report operative mortality to be higher in surgical urgency, we found urgent procedure to be the most significant risk factor for operative death.…”
Section: Operative Mortality and Morbiditycontrasting
confidence: 93%
See 4 more Smart Citations
“…Multivariate logistic regression analysis showed that the only preoperative risk factors associated with operative mortality were urgent procedure, associated coronary artery surgery, NYHA functional class, and previous percutaneous valvuloplasty. While Collart et al [11] did not report operative mortality to be higher in surgical urgency, we found urgent procedure to be the most significant risk factor for operative death.…”
Section: Operative Mortality and Morbiditycontrasting
confidence: 93%
“…Our postoperative complication rate was somewhat high (60%), but comparable to the recent series of Collart et al [11] who reported a morbidity of 63%. Pulmonary insufficiency or infection was one of the leading causes of postoperative morbidity.…”
Section: Operative Mortality and Morbiditysupporting
confidence: 89%
See 3 more Smart Citations